Interference Between Respiratory Syncytial Virus and Human Rhinovirus Infection in Infancy. (24th March 2017) - Achten, Niek B.; Wu, Pingsheng; Bont, Louis; Blanken, Maarten O.; Gebretsadik, Tebeb; Chappell, James D.; Wang, Li; Yu, Chang; Larkin, Emma K.; Carroll, Kecia N.; Anderson, Larry J.; Moore, Martin L.; et al.
Abstract: Background: Respiratory syncytial virus (RSV) and human rhinovirus (HRV) are the most common viruses associated with acute respiratory tract infections in infancy. Viral interference is important in understanding respiratory viral circulation and the impact of vaccines. Methods: To study viral interference, we evaluated cases of RSV and HRV codetection by polymerase chain reaction in 2 prospective birth cohort studies (the Infant Susceptibility to Pulmonary Infections and Asthma Following RSV Exposure [INSPIRE] study and the Tennessee Children's Respiratory Initiative [TCRI]) and a double-blinded, randomized, controlled trial (MAKI), using adjusted multivariable regression analyses. Results: Among 3263 respiratory tract samples, 24.5% (798) and 37.3% (1216) were RSV and HRV positive, respectively. The odds of HRV infection were significantly lower in RSV-infected infants in all cohorts, with adjusted odds ratios of 0.30 (95% confidence interval [CI], .22–.40 in the INSPIRE study, 0.18 (95% CI, .11–.28) in the TCRI (adjusted for disease severity), and 0.34 (95% CI, .16–.72) in the MAKI trial. HRV infection was significantly more common among infants administered RSV immunoprophylaxis, compared with infants who did not receive immunoprophylaxis (OR, 1.65; 95% CI, 1.65–2.39). Conclusions: A negative association of RSV on HRV codetection was consistently observed across populations, seasons, disease severity, and geographical regions. Suppressing RSV infection by RSV immunoprophylaxis might increase the risk of having HRV infection.